2016
DOI: 10.2139/ssrn.2752965
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Advertising Effectiveness of Creative Television Advertisements for High Involvement Products

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…When consumers encounter information overload, they use others' purchase data as heuristics (Simpson, Siguaw, & Cadogan, 2008). As consumers' involvement increases, consumers' appetite for getting information increases (Ali, 2016) and, as a result, the use of heuristics reduces (Cheung, Xiao, & Liu, 2012). It can be concluded that consumers under low involvement are more likely to follow herding cues such as customer rating and historic sales compared to high involvement situations.…”
Section: Perceived Riskmentioning
confidence: 99%
“…When consumers encounter information overload, they use others' purchase data as heuristics (Simpson, Siguaw, & Cadogan, 2008). As consumers' involvement increases, consumers' appetite for getting information increases (Ali, 2016) and, as a result, the use of heuristics reduces (Cheung, Xiao, & Liu, 2012). It can be concluded that consumers under low involvement are more likely to follow herding cues such as customer rating and historic sales compared to high involvement situations.…”
Section: Perceived Riskmentioning
confidence: 99%
“…Furthermore, Dahlén et al (2008) reported that by representing a greater effort on behalf of the advertiser and a greater ability of the brand, advertising creativity increases brand preference and perceived brand quality. Ultimately, creative advertisements seem to be a successful tactic for achieving more effectiveness than standard (less creative) advertisements as the former are more likely to be recalled (e.g., Till & Baack, 2005), induce positive emotions and favorable attitudes in consumers (Ali, 2016; Lehnert et al, 2013; Smith et al, 2008), evoke a stronger purchase intent or desire (Feltham & Arnold, 1994; Moorman et al, 2002; Shaouf et al, 2016), and are more effective in attracting attention (e.g., Sajjacholapunt & Ball, 2014) and facilitating brand extension (Ang et al, 2007; Till & Baack, 2005).…”
Section: Introductionmentioning
confidence: 99%